2010
DOI: 10.4166/kjg.2010.56.6.353
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Intraabdominal Cystic Lymphangioma in Korea

Abstract: Background/Aims: Cystic lymphangioma is an uncommon disease, and rarely develops in the intraabdomen. The aim of this article was to discuss about clinical characteristics of intraabdominal cystic lymphangioma developed in Korea. Methods: Age, sex, symptoms, locations and size of the lesions, diagnostic methods, treatments, complications and recurrence were analyzed in 13 pathologically confirmed cases of intraabdominal cystic lymphangioma and 18 cases of literature consideration reported in Korea. Results: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…(4,5,13) The sizes of these tumors were 5, 9 and 20 cm, respectively. While the 5 and 9 cm tumors were resected by omental excision without gastrectomy, the 20 cm tumor required gastrectomy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(4,5,13) The sizes of these tumors were 5, 9 and 20 cm, respectively. While the 5 and 9 cm tumors were resected by omental excision without gastrectomy, the 20 cm tumor required gastrectomy.…”
Section: Discussionmentioning
confidence: 97%
“…To date, various sizes and locations of MCLs have been reported, and intestinal resection is rarely required to pathologically diagnose and cure them. (4,5)…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the disseminated peritoneal cystic lymphangiomatosis is a rare form of the disease. It might mimic peritoneal carcinosis, and it is usually associated with mediastinal lesions and chylothorax [ 7 , 10 ]. Abdominal US, CT, and exploratory laparoscopy may be helpful in establishing the diagnosis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this was the largest retroperitoneal lymphangioma successfully treated with surgical excision to date in South Korea. A previous review based on intra-abdominal cystic lymphangiomas in Korea published in 2010 reported cases of intra-abdominal lymphangioma with the largest retroperitoneal cyst sized at 10 cm; the largest intra-abdominal cystic lymphangioma reported was 20 cm, originating in the pancreas tail[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initially asymptomatic, the mass eventually caused mass effect symptoms, leading the patient to opt for surgical treatment. This article presents the largest retroperitoneal lymphangioma treated with complete surgical excision in South Korea, compared to previous literature[ 7 ].…”
Section: Introductionmentioning
confidence: 99%